The Effect of Work Preparation Sheet Learning Media on Learning Outcomes of Turning Practice into Machining Practice in Vocational High Schools - Siraj, Siraj; Dabet, Abubakar; Syahputra, Azhar; Marwan, Marwan; Fajriana, Fajriana; Nasrah, Sayni (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2022)
This study aims to determine the learning outcomes of students' lathe practices who are taught by using work preparation sheets and not using the work preparation sheets in turning practice. It is also to find out the differences in the learning outcomes of students in both classes during machining practice-training courses at the eleventh grade of SMK Negeri 1 Bireuen. The research method used was a True Experimental Design research method in which the implementation used a Posttest-Only Control Design type that compares the experimental class with the control class. The population in this study was class XI TPM Mechanical Engineering at SMK Negeri 1 Bireuen which consisted of 2 classes with 58 students. Class XI TPM 1 was selected as the experimental class and class XI TPM 2 as the control class. The data collection was obtained from the results of the lathe practice. The results showed that the students of class XI TPM1 (experimental class) obtained an average value of turning the practice of 85.62. While the learning outcomes of class XI TPM2 students (control class) obtained an average value of 62.78 lathe practice. From these results, it can be concluded that learning outcomes using work preparation sheet learning during practice are better than those who do not use work preparation sheets during lathe practice.